Vaccines and diagnostic tools for animal health: The influence of biotechnology - McKeever, Declan J.; Rege, J.E.O. (Elsevier, 1999)
Development of improved vaccine and diagnostic-based disease control strategies has benefited considerably from advances in biotechnology, particularly those relating to recombinant DNA technology. Efficiency of the vaccine development process has been increased at all levels, from the analysis of immune responses to the production and delivery of protective antigens to the target species. Serological analysis of antibody prevalence has also become more straightforward as a result of the availability of recombinant pathogen proteins. However, greatest advances arising from biotechnological development relate to the detection and characterisation of pathogens in infected hosts. Probably the most significant development in this regard, which impacts both vaccine and diagnostic development, is the polymerase chain reaction. With the advent of DNA-based antigen delivery vehicles, it is conceivable that protein-based vaccine and diagnostic systems will have been superseded by DNA-based systems by the middle of the 21st century.